Toxic pollution and labour markets: Uncovering Europe's left-behind places - Charlotte Bez; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
This paper looks at the nexus between toxic industrial pollution and the spillovers from the plant's production activities, leading to regional lock-ins. Geolocalised facility-level data from the European Pollutant Release and Transfer Register (E-PRTR) are used to calculate annual chemical-specific pollution, weighted by its toxicity. We combine the latter with regional data on employment, wages and demographics sourced from Cambridge Econometrics, covering more than 1.200 NUTS-3 regions in 15 countries, over the period 2007-2018. We employ quantile regressions to detect the heterogeneity across regions and understand the specificities of the 10th and 25th percentiles, the so-called left-behind places. Our first contribution consists in giving a novel and comprehensive account of the geography of toxic pollution in Europe, both at facility and regional level, disaggregated by sectors. Second, we regress toxic pollution (intensity effect) and pollutant concentration (composition effect) on labour market dimensions of left-behind places. Our results point to the existence of economic dependence on noxious industrialization in left-behind places. In addition, whenever environmental efficiency-enhancing production technologies are adopted this leads to labour-saving effects in industrial employment, but positive spatial spillovers at the regional level. Through the lens of evolutionary economic geography our results call for a new political economy of left-behind places.
Keywords: Q52; P18; R11; O3; 330; Environmental inequality; Left-behind places; Toxic pollution; Labour markets